Study on the coating material of hexamethylol melamine modified phenolic resin for casting filter. Issue 44 (30th August 2022) - Tang, Yaoji; Huang, Renhe; Yuan, Zhenfei
Abstract: In this article, hexamethylol melamine (HMM) modified phenolic resin (PF) coating material was prepared by using thermoplastic PF wastewater. Using alcohol soluble PF, the thermoplastic PF wastewater (containing oxalic acid catalyst), methanol and HMM as raw materials, HMM was methyl etherified by oxalic acid and then modified PF was synthesized. By determination of carbon residue, thermogravimetric analysis (TGA) and differential scanning calorimetry, the influences on the heat resistance of modified PF by the composition of wastewater, composition of melamine formaldehyde (MF) resin, and composition of MF resin modified PF were analyzed. The results showed that the phenol content in wastewater had no effect on the heat resistance. The MF resin modified by HMM with the highest molar ratio of formaldehyde and melamine had the highest heat resistance. And the nitrogen content of the highest thermostable modified PF was 5 wt%. Additional curing agent was not required for HMM modified PF. The possible pyrolysis process was discussed. As a filter coating material, the heat resistance of HMM modified PF was better than that of PF cured with traditional urotropine (HMTA). Abstract :